Observations of thunderstorm outflows from Doppler radar and surface mesonetwork data - Dattore, Robert Edward, author; Sinclair, Peter C., author (Colorado State University. Libraries, 1989)
Observations of thunderstorm outflows and gust fronts are made from Doppler radar and surface mesonetwork data. These data are used to determine the validity of the assumption of mass balance for the outflow-downdraft system, and to assess the accuracy of the empirical relationship derived from density current theory in predicting the propagation speed of the gust front. In addition, the combination of radar and surface data are used for analysis of the outflow and gust front, and several features which are characteristic of outflows and gust fronts are revealed by these analyses. The data used are taken from two experiments which were designed for studying thunderstorms and outflows. These programs are the Microburst and Seyere Thunderstorm (MIST) program of Summer, 1986, operated near Huntsville, AL, and the Convective Initiation and Downburst Experiment (CINDE) of Summer, 1987, operated near Denver, CO. Both programs had associated research Doppler radars, surface mesonetworks, and some sounding systems. From these data, eight outflow gust front cases were obtained, three from MIST and five from CINDE. It is believed that this study represents the largest collection of Doppler radar and surface mesonetwork supported outflow-gust front cases to date. The results of this study show that from mass balance for the outflow-downdraft system, reasonable calculations of the downdraft speed required for this mass balance to be realized a.re obtained. These calculations are determined to be reasonable by comparison with downdraft speeds observed by previous researchers from aircraft penetrations and numerical modelling studies. The empirical density current approximation is found to be inadequate in predicting the gust front speeds of this study, with some errors as much as 50% and an average error of 37%. It is found that, in addition to the hydrostatic pressure difference across the gust front, the airflow within the outflow and in the environment also significantly affect the gust front propagation speed, and the density current equation is modified to include these effects. This modified equation is then found to produce a different value for k than has been agreed upon previously by researchers. With the new k-value and the above modifications, the density current approximation predicts the gust frontal speeds with a maximum error of 12% and an average error of 5%, exhibiting significant improvement over the unmodified density current relationship. The analyses derived from the radar and surface data reveal a variety of characteristics of thunderstorm outflows and gust fronts which have been previously observed. These include the marked gradients in temperature, dewpoint, wind speed, and pressure which exist across the front, as well as convergence along the entire length of the front and at gust front intersection points. so noted is rotation in bends and clefts in the front, and in the analyses in which downdrafts are present, the downdrafts are observed to always be characterized by anticyclonic rotation.
March 1989.
Also issued as Robert Edward Dattore's thesis (M.S.) -- Colorado State University, 1989.
Keywords: Thunderstorms; Thunderstorms -- Observations; Gust loads -- Measurement; Doppler radar